Material Analysis of the vocabulary of the Guarani Language of 1722: A Jesuit-Guaraní print - Fernandez Rojo, Analía (Encontros Bibli: revista eletrônica de biblioteconomia e ciência da informação, 2020)
Objective: It aims to undertake a material analysis of one of the forms born from the mythical Jesuit-Guarani press. Method: It makes a material analysis of the bibliographic state of the copy of the Vocabulary of the Guaraní language of Ruiz de Montoya printed in 1722 in the Santa María la Mayor printing house, which is currently kept in the Mariano Moreno National Library in order to identify details that give us clues about possible editorial practices at that time. Result: Taking into account what is presented in this work, what is already known about the economic, political and social structure of the Jesuit-Guaraní communities, about the political force that implied the presence of a printing press in those lands Conclusions: It infers that the Jesuit-Guaraní traveling printing press was a school printing press and that its main cause of mobility lies in this fact, added to the impossibility of manufacturing other printing presses in each town. Keywords: Guaraní Language Vocabulary - Ruiz de Montoya. Jesuit-Guarani Press. Material analysis. Mariano Moreno National Library – Argentina.